STRESS AMONG PATIENTS ON REGULAR HEMODIALYSIS AT ELJMEEH CENTER IN DONGOLA TOWN- SUDAN 2022 - Mohamed Eman Saif, Sadeg Aldeen; Abdelrahim Abugroon, Basim Al Zubair; Mohamed Ahmed, Doaa Kamal; Jomaa Ismael, Romaisa Ismael; Almofadel Ahmed, Faiza Mohamed; Hussin Taha, Marvat Abdallah; Mohmmed Ahmed Abdallah, Higazi; Akasha Mohammed, Abdualrahman; Yagoub, Anwer ALnour (International Journal of Research -GRANTHAALAYAH, 2023)
Background: stress is commonly reported among dialysis patients, but their prevalence and correlates vary by sociocultural context. Objective: The aim of this study is to determine the level of stress and associated factors among patients receiving hemodialysis at ELJMEEH CENTER in DONGOLA town. Method: Descriptive cross-sectional design was used. 90 patients receiving hemodialysis were included. The patients were interviewed while undergoing their dialysis session using the perceived stress scale. verbal and written consent was taken. The data was analyzed by SPSS program and presented in tables and figures. Result: there was no significant statistical relationship between demographic data of the study group and stress level, except with patient resident P value (0.022). More than half of the study group were male, living in villages, there level of education as for as primary or secondary. Conclusion: There is no statistical relationship between stress and demographic data except in education and the total level of stress was moderate.